Nghiên cứu thành phần hóa học của cây xáo leo Paramignya scandens - Toàn Phan, Nguyễn Hữu; Diệu Thuần, Nguyễn Thị; Duy, Nông Văn; Ngọc, Ninh Thị; Thanh, Nguyễn Văn; Cường, Nguyễn Xuân; Nam, Nguyễn Hoài; Kiệm, Phan Văn; Minh, Châu Văn (Vietnam Journal of Chemistry, 2015)
Phytochemical investigation of the methanol extract of Paramignya scandens led to isolation of seven compounds including: a limonoid methyl isolimonate (1); a flavonone diglycoside atripliside B (2); a phenyl derivative trans-N-p-coumaroyl tyramine (3); two megastigmane glycosides gusanlungionoside C (4) and (6R,9S)-roseoside (5); a lignan glycoside syringaresinol di-O-β-D-glucopyranoside (6); and a nucleoside adenosine (7). Their structures were elucidated by 1D and 2D NMR experiments. This is the first report of these compounds from P. scandens.